POTENSI TEPUNG PISANG KAPAS SEBAGAI SUMBER PATI RESISTEN MELALUI MODIFIKASI DI TINGKAT PATI - Sukmiyati Agustin (PROSIDING SEMINAR KIMIA, 2014)
Studies on the potential of kapas banana (Musa comiculata) flour as resistant starch source were carried out through analysis of resistant starch content and starch digestibility on the native and modified banana flour. Native banana flour was prepared by drying the banana slice, ground and passed through an 80 mesh screen. Modified banana flour was produced by spontaneous fermentation (roo m temperature; 0,2, 24 and 36 ) and a toclaving ( 2  ̊C; 0, 5, 30 and 45 min) of t e banana slices before drying process. The modification processes influenced the amount of resistant starch and its digestibility. Spontaneous fermentation up to 12 h and autoclaving up to 30 min increased the resistant starch content and digestibility of kapas banana flour produced.